Благодійники та меценати на Запоріжжі (ХІХ ст.) (Zaporizhzhia Historical Review, 2021)
The article points at the fact that in the XIXth century new forces appeared on historical arena – industrialists and intelligentsia, who took upon themselves patronage of arts and charity activities. The aim of the article is to generalize the material about the patrons of Zaporizhzhya region, to explore the directions, forms and motives of charity activities, to name the patrons and benefactors, to stress certain specificity of charity activities in the region.